Собачье сердце: [повести] / Михаил Булгаков - Булгаков Михаил Афанасьевич (Всемирная литература (с картинкой), 2021)
Экземпляры: (20230124) / Инвентарный номер: 41705 / Цена: 205.81 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Б 90 / ГРНТИ: 17 / ББК: 84(2=411.2)6-44